Games for active ageing, well-being and quality of life: a pilot study. Issue 8 (3rd August 2018) - Costa, Liliana Vale; Veloso, Ana Isabel; Loizou, Michael; Arnab, Sylvester
ABSTRACT: The goal of this study is to identify a set of psychosocial variables and design domains important for game designers to encourage active ageing, well-being and quality of life. Sixty adult learners at four universities of third age were randomly assigned to three groups: the experimental group (G1), who tested firstly a game-based learning platform (GBLP) and then a computer-assisted platform (CAP); the comparison group (G2), who tested firstly the CAP and then the GBLP and the control group (G3) that did not take part in the intervention. Participants were assessed on their health-related well-being and quality of life, using the SF36v2 and WHOQOL-BREF scales before and after each experiment. Findings suggest that there were differences between the group type and their perception on mental health ( F (2, 57) = 3.771, p = .029) and general health-related well-being ( F (2, 57) = 5.231, p = .008), in which the GBLP showed improvements relative to the CAP. The environment and mental health were some of the psychosocial domains that should be considered, whereas storytelling, context-aware challenges, game space, immediate feedback, role-playing and social engagement were relevant design domains for these games.